Induced unconventional superconductivity on the surface states of Bi2Te3 topological insulator. Issue 1 (December 2017) - Charpentier, Sophie; Galletti, Luca; Kunakova, Gunta; Arpaia, Riccardo; Song, Yuxin; Baghdadi, Reza; Wang, Shu Min; Kalaboukhov, Alexei; Olsson, Eva; Tafuri, Francesco; Golubev, Dmitry; Linder, Jacob; et al.
Abstract Topological superconductivity is central to a variety of novel phenomena involving the interplay between topologically ordered phases and broken-symmetry states. The key ingredient is an unconventional order parameter, with an orbital component containing a chiralp x + ip y wave term. Here we present phase-sensitive measurements, based on the quantum interference in nanoscale Josephson junctions, realized by using Bi2 Te3 topological insulator. We demonstrate that the induced superconductivity is unconventional and consistent with a sign-changing order parameter, such as a chiralp x + ip y component. The magnetic field pattern of the junctions shows a dip at zero externally applied magnetic field, which is an incontrovertible signature of the simultaneous existence of 0 andπ coupling within the junction, inherent to a non trivial order parameter phase. The nano-textured morphology of the Bi2 Te3 flakes, and the dramatic role played by thermal strain are the surprising key factors for the display of an unconventional induced order parameter. Proximity effect may induce unconventional superconductivity in the topologically protected surface states of a topological insulator, however experimental evidence remains rare. Here, Charpentier et al. report proximity effect induced superconductivity in nanoscale Josephson junctions and suggest an unconventionalp -wave order parameter.